Development of real time environment monitoring system using with MSP430 - Kommuri, Krishnaveni; Venkata Ratnam, k; Prathyusha, Geetha; Gopi Krishna, p (International Journal of Engineering and Technology, 2018)
This paper specifies about the monitoring environmental parameters regularly to forecast the weather prediction. Nowadays, Weather prediction plays a vital role for citizens living in the coastal areas. Mostly the parameters of the weather prediction vary to different fields and areas which hep the agricultures and travelers. This application makes the system more reliable, accurate, and flexible and dynamically varies the parameters of environment. We mainly consider the two factors; one is to acquire the parameter value accurately and second is to monitor continuously acting with reliability. The Environmental parameters considered in this paper are temperature and humidity, atmospheric pressure and light intensity. The MSP430 Micro controller observes the parameters by which the threats can be easily identified by the users and get alerted from the situations.
Keywords: Use about five key words or phrases in alphabetical order; Separated by Semicolon.